Fatty acid composition of lipids from Ugandan green coﬀee beans - Bamuwamye, Michael; Mugabe, Amos; Nakisozi, Henriettah; Byarugaba-Bazirake, George William; Ogwok, Patrick (Food Agricultural Sciences and Technology, 2025)
The study assessed the lipid content of green Coffea arabica and Coffea canephora var. robusta beans, the fatty acid (FA) composition of the lipids, and their nutritional quality to provide a basis for utilization. The green coffee beans (GCB) were obtained from the Uganda Coffee Development Authority (UCDA) and coffee dealers. Lipid was extracted in a Soxhlet apparatus using n-hexane. Fatty acids were determined as the FA methyl esters using gas chromatography with flame ionization detector (GC-FID). Differences in lipid content were analyzed using one-way analysis of variance (ANOVA). The polyunsaturated FA; PUFA/saturated fatty acid; SFA (PUFA/SFA), palmitic acid; PA/PUFA, and ω6:ω3 ratios were used to evaluate the nutritional quality of the GCB lipids. Lipid content ranged between 1.75 and 15.45%. Higher lipid content was obtained for C. arabica than for C. canephora. Unsaturated FA (UFA) predominated over SFA. Linoleic acid (LA; 18:2ω6) and oleic acid (OA; 18:1ω9) were the main UFA and accounted for 50–60% of the total FA. Palmitic acid (16:0) was the major SFA. The PUFA/SFA ratio was within the desired range. Fifty-eight percent of the samples had PA/PUFA ratio < 1. The ω6/ω3 ratio was higher than the recommendation of 1:1 to 4:1 for a healthy diet. Information on the FA composition of coffee lipids will provide a basis for their industrial utilization. Coffee lipid can be a source of 16:0 and 18:2ω6 that can be used in food and as an excipient in drug preparations, respectively.